Highly thermally conductive current collector for secondary batteries

By adding carbon silicide particles to the polymer film layer of the current collector of lithium-ion battery composite, and plated with a high-purity metal layer, the problem of insufficient thermal conductivity in the prior art is solved, and efficient thermal management of lithium-ion batteries under thermal stimulation is achieved.

JP3251065UActive Publication Date: 2025-04-25YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024600185U
Authority / Receiving Office
JP · JP
Patent Type
Utility models
Current Assignee / Owner
Priority Date
2022-05-13
Filing Date
2022-06-02
Publication Date
2025-04-25
Estimated Expiration
2032-06-02

AI Technical Summary

Technical Problem

The current collector of the composite lithium-ion battery has insufficient heat conduction, which leads to the inability to transmit and release heat in time, which easily causes the heat runaway phenomenon.

Method used

High thermal conductivity current collectors are formed by uniformly mixing polymer and carbon silicide particles in the polymer film layer and plating high-purity metal aluminum or copper layers on both sides of the polymer film layer.

Benefits of technology

It improves the thermal conductivity of the polymer film layer, enhances the thermal conductivity of the overall current collector, ensures that the lithium-ion battery can transmit and release heat in a timely manner under thermal stimulation, and avoids the occurrence of thermal runaway phenomenon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0003251065000001_ABST
    Figure 0003251065000001_ABST
Patent Text Reader

Abstract

The high thermal conductive current collector of the secondary battery includes a polymer thin film layer, and two opposite surfaces of the polymer thin film layer are provided with metal plating layers. The polymer thin film layer includes a homogeneously mixed polymer and silicon carbide particles. The present invention uses a mixture of a polymer and silicon carbide particles, and the silicon carbide particles have stable chemical properties, high thermal conductivity, low thermal expansion coefficient, good wear resistance and other properties, so that the thermal conductive ability of the polymer thin film layer containing silicon carbide particles can be improved, and the overall thermal conductivity of the product can be improved. When the battery receives heat, the heat can be transferred out in a timely manner, and the occurrence of thermal runaway in the battery can be effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for manufacturing a highly thermally conductive current collector for secondary batteries. [Background technology]

[0002] Currently, there are two types of composite current collectors: copper current collectors and aluminum current collectors. The copper current collectors and aluminum current collectors are both made of two parts, including a polymer thin film layer in the middle and a metal plating layer on the two surfaces opposite the polymer thin film layer. The current collectors are manufactured by a vacuum deposition process, but the thermal conductivity of the polymer thin film layer is relatively poor, so the overall thermal conductivity of the composite current collector is relatively poor. When the battery receives heat, the heat cannot be transferred out in a timely manner, and the battery is prone to thermal runaway. Summary of the Invention [Problem to be solved by the invention]

[0003] Therefore, it is necessary to provide a method for manufacturing a highly thermally conductive current collector for a secondary battery that can improve the thermal conductivity of the polymer thin film layer, thereby improving the overall thermal conductivity of the product and effectively preventing the occurrence of thermal runaway in the battery. [Means for solving the problem]

[0004] The polymer thin film layer includes a metal plating layer provided on two opposite surfaces of the polymer thin film layer, The polymer thin film layer comprises a homogeneously mixed polymer and silicon carbide particles.

[0005] By mixing the high molecular weight polymer with the silicon carbide particles, since the silicon carbide particles have properties such as stable chemical performance, high thermal conductivity, low thermal expansion coefficient, and good wear resistance, the thermal conduction ability of the polymer thin film layer containing the silicon carbide particles can be improved, and the overall thermal conductivity of the product can be improved. When the battery receives heat, the heat can be transmitted and discharged in a timely manner, and the occurrence of thermal runaway in the battery can be effectively avoided.

[0006] In one embodiment, the relative molecular mass of the polymer is 500,000 to 1,000,000 Mr.

[0007] In one embodiment thereof, the mass ratio of the polymer to the silicon carbide particles is 10:1 to 20:1.

[0008] In one embodiment, the polymer thin film layer has a pin puncture strength of 100 gf or more, an MD stretch strength of 180 MPa or more, a TD stretch strength of 180 MPa or more, an MD elongation of 10% or more, and a TD elongation of 10% or more.

[0009] In one embodiment, the metal plating layer is a metal aluminum layer or a metal copper layer.

[0010] In one embodiment, the purity of the metal plating layers is 99.8% or more.

[0011] In one embodiment, the polymer comprises at least one of an insulating polymer material, an insulating polymer composite material, a conductive polymer material, and a conductive polymer composite material.

[0012] Among them, the insulating polymer material includes at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PPE), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), polyparaphenylene terephthalamide (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, derivatives thereof, crosslinked bodies thereof, and copolymers thereof.

[0013] The insulating polymer composite material is a composite material made of an insulating polymer material and an inorganic material, where the inorganic material can be at least one of a ceramic material, a glass material, and a ceramic composite material.

[0014] The conductive polymer material employs at least one of doped polythiazyl and doped polyacetylene.

[0015] The conductive polymer composite material employs a composite material made of an insulating polymer material and a conductive material.

[0016] In one embodiment thereof, the polymer thin film layer has a thickness ranging from 1 μm to 25 μm, and the metal plating layer has a thickness ranging from 0.5 μm to 1.5 μm.

[0017] The present application relates to a method for producing a highly thermally conductive current collector for the above-mentioned secondary battery, homogeneously mixing the polymer and the silicon carbide particles to form a silicon carbide doped polymeric material; performing a casting operation on the silicon carbide doped polymeric material to form the polymeric thin film layer; and depositing the metal plating layers on two opposite surfaces of the polymer thin film layer, respectively.

[0018] In one embodiment, the silicon carbide doped polymer material is cast to form a semi-polymeric thin film layer, and the semi-polymeric thin film layer is biaxially stretched and divided to form the polymeric thin film layer. Effect of the Invention

[0019] In the above-mentioned embodiment, by mixing the high molecular weight polymer with silicon carbide particles, the silicon carbide particles have stable chemical properties, high thermal conductivity, low thermal expansion coefficient, good wear resistance, etc., so that the thermal conductivity ability of the polymer thin film layer containing silicon carbide particles can be improved, and the overall thermal conductivity of the product can be improved. When the battery receives heat, the heat can be transferred out in a timely manner, and the occurrence of thermal runaway in the battery can be effectively avoided. The metal plating layer is a metal aluminum layer or a metal copper layer, and the purity of the metal plating layer 300 is 99.8% or more. The high purity metal aluminum layer has properties such as low deformation resistance, high electrical conductivity, and good plasticity, and the high purity metal copper layer has good ductility, thermal conductivity, and electrical conductivity. [Brief description of the drawings]

[0020] [Figure 1] 2 is a schematic diagram showing the structure of a highly thermal conductive current collector of a secondary battery according to an embodiment of the present invention; [Diagram 2] 2 is a flow chart showing steps of a method for manufacturing a highly thermal conductive current collector for a secondary battery according to an embodiment of the present invention. [Diagram 3] 2 is a flow chart showing steps of a method for manufacturing a composite current collector according to a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The drawings constituting a part of this application are used to provide a further understanding of the present invention, and the illustrative embodiments of the present invention and the description thereof are intended to interpret the present invention and are not intended to unduly limit the present invention.

[0022] In order to more clearly describe the technical solutions in the embodiments of the present invention, the drawings that need to be used in the description of the embodiments are briefly described below. The drawings in the following description are some embodiments of the present invention, and it is obvious to those skilled in the art that they can obtain other drawings according to these drawings without paying creative labor.

[0023] In order to more clearly explain the above objects, features and advantages of the present invention, the following detailed description of the specific embodiment of the present invention will be given with reference to the drawings. In order to fully understand the present invention, many specific details are described in the following description. However, the present invention is not limited by the specific embodiment disclosed below, because the present invention can be implemented in other ways different from those described herein, and those skilled in the art can make similar improvements without departing from the spirit of the present invention.

[0024] In the description of the present invention, the orientations and positional relationships indicated by terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. are based on the orientations and positional relationships shown in the drawings, and are merely intended to facilitate and simplify the description of the present invention, and are not intended to indicate or suggest that the devices or elements mentioned have a specific orientation and must be configured and operated from a specific orientation. Therefore, they should not be understood as limiting the present invention.

[0025] Additionally, the terms "first" and "second" are merely for descriptive purposes and should not be understood as implicitly indicating the number of the designated technical features, indicating or suggesting their relative importance. Thus, a feature qualified as "first" or "second" may explicitly or implicitly include at least one of the feature. In the description of the present invention, "plurality" means at least two, e.g., two, three, etc., unless otherwise limited.

[0026] In the description of the present invention, the terms "attached", "connected", "connected" and "fixed" should be understood in a broad sense unless otherwise clearly specified or limited. For example, they may be fixedly connected, detachably connected or integral, mechanically connected, electrically connected, directly connected, indirectly connected via an intermediate medium, or communicated inside two parts or interacting with each other. Those skilled in the art can understand the specific meanings of the above terms in the present invention according to the specific circumstances.

[0027] In the present invention, unless otherwise clearly specified or limited, a first feature being "above" or "below" a second feature may mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature via an intermediate medium. Furthermore, a first feature being "above," "above," and "on the upper surface" of a second feature means that the first feature may be directly above and diagonally above the second feature, or simply that the first feature is higher in horizontal height than the second feature. A first feature being "below," "below," and "on the lower surface" of a second feature means that the first feature may be directly below and diagonally below the second feature, or simply that the first feature is lower in horizontal height than the second feature.

[0028] It should be noted that when an element is referred to as being "fixed" or "mounted" on another element, it may be directly on the other element, or there may be intervening elements present. When an element is referred to as being "connected" to another element, it may be directly connected to the other element, or there may be intervening elements present at the same time. As used herein, the terms "vertical," "horizontal," "upper," "lower," "left," "right," and similar terms are merely for descriptive purposes and do not represent the only embodiments.

[0029] 1, one embodiment of the present invention provides a highly thermally conductive current collector 10 for a secondary battery, comprising a polymer thin film layer 100 having metal plating layers 300 formed on two opposite surfaces of the polymer thin film layer 100, the polymer thin film layer 100 including a uniformly mixed polymer 110 and silicon carbide particles 120. Specifically, the powder particle size of the silicon carbide particles 120 is 0.5 μm.

[0030] Specifically, the silicon carbide particles 120 have properties such as stable chemical properties, high thermal conductivity, low thermal expansion coefficient, and good wear resistance. By uniformly mixing the silicon carbide particles 120 with high thermal conductivity and the polymer 110, the thermal conduction ability of the polymer thin film layer 100 can be increased, and the overall thermal conductivity of the product can be improved.

[0031] The high thermal conductive current collector 10 of the secondary battery has a puncture strength of 50 gf or more, an MD elongation strength of 150 MPa or more, a TD elongation strength of 150 MPa or more, an MD elongation rate of 10% or more, and a TD elongation rate of 10% or more. Exemplarily, the high thermal conductive current collector 10 of the secondary battery has a puncture strength of 80 gf, an MD elongation strength of 200 MPa, and a TD elongation strength of 200 MPa. The MD elongation rate is 50% and the TD elongation rate is 50%. Note that MD (Machine Direction) refers to the vertical direction, and TD (Transverse Direction, perpendicular to the mechanical direction) refers to the horizontal direction.

[0032] Referring to FIG. 1, according to some embodiments of the present application, preferably, in this embodiment, the relative molecular mass of the high molecular weight polymer 110 is 500,000 to 1,000,000 Mr. In other possible embodiments, the relative molecular mass of the high molecular weight polymer 110 may be in other numerical ranges. For example, the relative molecular mass of the high molecular weight polymer 110 may be 10,000 to 500,000 Mr. Exemplarily, the relative molecular mass of the polymer thin film layer 100 is 400,000 Mr.

[0033] The relative molecular mass refers to the sum of the relative atomic masses (Ar) of each atom in a chemical formula. In the present application, the relative molecular mass of the high molecular polymer 110 is not limited. For example, the relative molecular mass of the high molecular polymer 110 is 600,000 Mr.

[0034] Referring to FIG. 1, according to some embodiments of the present application, the mass ratio of the polymer 110 to the silicon carbide particles 120 is preferably 10:1 to 20:1. That is, in the polymer thin film layer 100, the ratio of the polymer 110 is far greater than the ratio of the silicon carbide particles 120. The upper limit of the mass ratio of the polymer 110 to the silicon carbide particles 120 in the polymer thin film layer 100 may be set according to the required thermal conductivity of the polymer thin film layer 100, and is not limited by the present application. However, the lower limit of the mass ratio of the polymer 110 to the silicon carbide particles 120 in the molecular thin film layer should not be lower than 10:1. Otherwise, the conductive performance of the polymer thin film layer 100 will be affected.

[0035] 1, according to some embodiments of the present application, the polymer thin film layer 100 preferably has a pin puncture strength of 100 gf or more, an MD stretch strength of 180 MPa or more, a TD stretch strength of 180 MPa or more, an MD elongation of 10% or more, and a TD elongation of 10% or more. Exemplarily, the polymer thin film layer 100 has a pin puncture strength of 300 f or more, an MD stretch strength of 400 MPa or more, a TD stretch strength of 400 MPa or more, an MD elongation of 50% or more, and a TD elongation of 50% or more.

[0036] In addition, in the present application, the upper limits of the pin puncture strength, MD stretching strength, TD stretching strength, MD elongation rate, and TD elongation rate of the polymer thin film layer 100 are not limited, and may be set according to the needs of use. The lower limit of the pin puncture strength of the polymer thin film layer 100 should not be lower than 100gf, the lower limit of the MD stretching strength should not be lower than 180MPa, the lower limit of the TD stretching strength should not be lower than 180MPa, the lower limit of the MD elongation rate should not be lower than 10%, and the lower limit of the TD elongation rate should not be lower than 10%. Otherwise, it will affect the mechanical performance of the polymer thin film layer 100, and ultimately affect the pin puncture strength, MD stretching strength, TD stretching strength, MD elongation rate, and TD elongation rate of the current collector.

[0037] Referring to FIG. 1, according to some embodiments of the present application, the metal plating layer 300 preferably adopts a metal aluminum layer or a metal copper layer. Specifically, the purity of the metal plating layer 300 is 99.8% or more. That is, the metal plating layer 300 in the present application adopts a high-purity metal. In one embodiment, the metal plating layer 300 adopts a metal aluminum layer, and the purity of the metal aluminum layer is 99.8% or more. The high-purity metal aluminum layer has properties such as low deformation resistance, high electrical conductivity, and good plasticity. In another embodiment, the metal plating layer 300 adopts a metal copper layer, and the purity of the metal copper layer is 99.8% or more. The high-purity metal copper layer has good ductility, thermal conductivity, and electrical conductivity.

[0038] The peel strength between the metal plating layer 300 and the polymer thin film layer 100 is 5 N / m or more. Exemplarily, the peel strength between the metal plating layer 300 and the polymer thin film layer 100 is 20 N / m. Since the peel strength between the metal plating layer 300 and the polymer thin film layer 100 is high, the metal plating layer 300 and the polymer thin film layer 100 are unlikely to fall off, thereby ensuring the electrical performance and safety of the battery.

[0039] Referring to FIG. 1, according to some embodiments of the present application, the polymer thin film layer 100 preferably includes at least one of an insulating polymer material, an insulating polymer composite material, a conductive polymer material, and a conductive polymer composite material.

[0040] Among them, the insulating polymer material includes at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PPE), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), polyparaphenylene terephthalamide (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, derivatives thereof, crosslinked bodies thereof, and copolymers thereof.

[0041] The insulating polymer composite material may be a composite material made of an insulating polymer material and an inorganic material, in which the inorganic material may be at least one of a ceramic material, a glass material, and a ceramic composite material.

[0042] The conductive polymer material may be at least one of doped polythiazyl and doped polyacetylene.

[0043] The conductive polymer composite material may be a composite material made of an insulating polymer material and a conductive material. Specifically, the conductive material may be at least one of a conductive carbon material, a metal material, and a composite conductive material. More specifically, the conductive carbon material is at least one selected from carbon black, carbon nanotubes, graphite, acetylene black, and graphene. The metal material is at least one selected from metallic nickel, metallic iron, metallic copper, metallic aluminum, or an alloy of the above metals. The composite conductive material is at least one selected from graphite powder coated with metallic nickel and carbon fiber coated with metallic nickel.

[0044] 1, according to some embodiments of the present application, the thickness range of the polymer thin film layer 100 is preferably 1 μm to 25 μm, and the thickness range of the metal plating layer 300 is preferably 0.5 μm to 2.5 μm. The thickness range of the highly thermally conductive current collector 10 of the secondary battery in the present application is 3 μm to 30 μm. Illustratively, the thickness of the polymer thin film layer 100 is 20 μm, and the thickness of the metal plating layer 300 is 1.5 μm.

[0045] Working Example The following examples are provided to more specifically describe the contents disclosed in the present invention, and these examples are provided for descriptive purposes only, and it is obvious to those skilled in the art that various modifications and changes may be made within the scope of the contents disclosed in the present invention. Unless otherwise specified, the parts, percentages and ratios described in the following examples are all based on weight, and all reagents used in the examples are all commercially available or can be synthesized by conventional methods, and can be used as is without the need for further processing. In addition, all equipment used in the examples are commercially available.

[0046] Referring to FIG. 2, an embodiment 1 of the present application further provides a method for manufacturing the high thermal conductive current collector 10 of the secondary battery described above, which includes the following steps.

[0047] Step 1: Select a 6 μm high molecular weight polymer 110, a 99.9% pure metal aluminum layer, and silicon carbide particles 120. The high molecular weight polymer 110 is polybutylene terephthalate (PET), the relative molecular mass of the high molecular weight polymer 110 is 600,000 Mr, and the powder particle size of the silicon carbide particles 120 is 0.5 μm.

[0048] Step 2: The polymer 110 and the silicon carbide particles 120 are mixed uniformly to form a silicon carbide doped polymer material, in which the mass ratio of the polymer 110 to the silicon carbide particles 120 is 20:1.

[0049] Step 3: The polymer material doped with silicon carbide was cast to form a polymer thin film layer 100. The device for casting the polymer material doped with silicon carbide is not the focus of this application, so the description thereof is omitted in this application. The polymer thin film layer 100 was formed by casting extrusion drawing.

[0050] Step 4: A metal aluminum layer with a purity of 99.9% was deposited on each of the two opposite surfaces of the polymer thin film layer 100. The metal aluminum layer had a thickness of 1 μm, and finally, a highly thermally conductive current collector 10 for a secondary battery with a thickness of 8 μm was manufactured. After the highly thermally conductive current collector 10 for a secondary battery was manufactured, the highly thermally conductive current collector 10 for a secondary battery was divided, wound and vacuum packaged. The highly thermally conductive silicon carbide particles 120 and the high molecular weight polymer 110 were uniformly mixed to manufacture the polymer thin film layer 100, thereby increasing the thermal conductivity of the polymer thin film layer 100 and improving the overall thermal conductivity of the product.

[0051] 1, according to some embodiments of the present application, preferably, a polymeric material doped with silicon carbide is cast to form a semi-polymeric thin film layer, and the semi-polymeric thin film layer is biaxially stretched and divided to form a polymeric thin film layer 100. Here, biaxial refers to the longitudinal and transverse directions of the polymeric thin film.

[0052] Example 2 Step 1: Select a 1 μm high molecular weight polymer 110, a 99.9% pure metal aluminum layer, and silicon carbide particles 120. The high molecular weight polymer 110 is polybutylene terephthalate (PET), the relative molecular mass of the high molecular weight polymer 110 is 500,000 Mr, and the powder particle size of the silicon carbide particles 120 is 0.5 μm.

[0053] Step 2: The polymer 110 and the silicon carbide particles 120 are mixed uniformly to form a silicon carbide doped polymer material, in which the mass ratio of the polymer 110 to the silicon carbide particles 120 is 10:1.

[0054] Step 3: The silicon carbide doped polymer material was cast to form a polymer thin film layer 100 .

[0055] Step 4: A metallic copper layer with a purity of 99.9% was deposited on each of the two opposite surfaces of the polymer thin film layer 100. Among them, the metallic aluminum layer had a thickness of 2.5 μm, and finally, a highly thermally conductive current collector 10 for a secondary battery with a thickness of 30 μm was manufactured.

[0056] Example 3 Step 1: Select a 1 μm high molecular weight polymer 110, a 99.9% pure metallic copper layer, and silicon carbide particles 120. The high molecular weight polymer 110 is polybutylene terephthalate (PET), the relative molecular mass of the high molecular weight polymer 110 is 1 million Mr, and the powder particle size of the silicon carbide particles 120 is 0.5 μm.

[0057] Step 2: The polymer 110 and the silicon carbide particles 120 are mixed uniformly to form a silicon carbide doped polymer material, in which the mass ratio of the polymer 110 to the silicon carbide particles 120 is 15:1.

[0058] Step 3: The silicon carbide doped polymer material was cast to form a polymer thin film layer 100 .

[0059] Step 4: A metallic copper layer with a purity of 99.9% was deposited on each of the two opposite surfaces of the polymer thin film layer 100. Among them, the metallic aluminum layer had a thickness of 1 μm, and finally, a highly thermally conductive current collector 10 for a secondary battery with a thickness of 3 μm was manufactured.

[0060] Comparative Example 1 With reference to FIG. 3, the method for producing the composite current collector according to this comparative example includes the following steps.

[0061] Step 1: A 6 μm polymer thin film layer 100 and a 99.9% pure metal aluminum layer are selected, where the polymer thin film layer 100 is made of polybutylene terephthalate (PET).

[0062] Step 2: The 6 μm polymer thin film layer 100 and the 99.9% pure aluminum metal layer are respectively placed in a vacuum deposition apparatus, and the aluminum metal layer is deposited on the two opposite surfaces of the polymer thin film layer 100 to obtain the required composite current collector, where the thickness of the aluminum metal layer is 1 μm in this embodiment.

[0063] Finally, a composite current collector having a thickness of 8 μm was produced. After the production of the composite current collector was completed, the composite current collector was divided, wound and vacuum packaged.

[0064] Comparative Example 2 The method for producing the composite current collector according to this comparative example includes the following steps.

[0065] Step 1: A 25 μm polymer thin film layer 100 and a 99.9% pure copper metal layer are selected, where the polymer thin film layer 100 is made of polybutylene terephthalate (PET).

[0066] Step 2: The 25 μm polymer thin film layer 100 and the 99.9% pure copper metal layer are respectively placed in a vacuum deposition apparatus, and aluminum metal layers are deposited on the two opposite surfaces of the polymer thin film layer 100 to obtain a composite current collector, where the thickness of the aluminum metal layer is 2.5 μm in this embodiment.

[0067] Finally, a composite current collector having a thickness of 10 μm was produced. After the production of the composite current collector was completed, the composite current collector was divided, wound and vacuum packaged.

[0068] The thermal conductivity of the highly thermally conductive current collectors 10 of the secondary batteries of Examples 1 to 3 and the composite current collectors of Comparative Examples 1 and 2 was measured, and the effect data shown in Table 1 was obtained.

[0069] Table 1 shows the measurement data of the solubility of the composite current collector 10.

[0070] [Table 1]

[0071] As can be seen from the above table, the thermal conductivity of the high thermal conductive current collector 10 of the secondary battery in the present invention is higher than that of the composite current collector of the comparative example. According to the above table, the thermal conductivity of the high thermal conductive current collector 10 of the secondary battery is related to the mass ratio of the polymer 110 to the silicon carbide particles 120 of the high thermal conductive current collector 10 of the secondary battery, and the larger the mass ratio of the polymer 110 to the silicon carbide particles 120, the lower the content of the silicon carbide particles 120, and the lower the thermal conductivity of the high thermal conductive current collector 10 of the secondary battery.

[0072] The technical features of the above embodiments can be combined in any way. For the sake of simplicity, all possible combinations of the technical features in the above embodiments are not described, but as long as there is no contradiction in the combination of these technical features, they should all be considered within the scope of the present specification.

[0073] It should be understood that the above examples are merely illustrative of some embodiments of the present invention, and the description is specific and detailed, but does not limit the scope of the invention. It should be noted that those skilled in the art can make some modifications and improvements without departing from the concept of the present invention, and all of these fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention is based on the scope of the attached claims. [Explanation of symbols]

[0074] 10: high thermal conductive collector; 100: polymer thin film layer; 110: polymer; 120: silicon carbide particles; 300: metal plating layer.

Claims

1. The polymer thin film layer includes a metal plating layer provided on two opposite surfaces of the polymer thin film layer, Wherein, the polymer thin film layer comprises a homogeneously mixed polymer and silicon carbide particles; A highly thermally conductive current collector for a secondary battery.

2. The relative molecular mass of the polymer is 500,000 to 1,000,000 Mr.

2. The highly thermally conductive current collector for a secondary battery according to claim 1.

3. The mass ratio of the polymer to the silicon carbide particles is 10:1 to 20:1; 2. The highly thermally conductive current collector for a secondary battery according to claim 1.

4. The polymer thin film layer has a pin puncture strength of 100 gf or more, an MD stretch strength of 180 MPa or more, a TD stretch strength of 180 MPa or more, an MD elongation percentage of 10% or more, and a TD elongation percentage of 10% or more.

2. The highly thermally conductive current collector for a secondary battery according to claim 1.

5. The metal plating layer is a metal aluminum layer or a metal copper layer.

2. The highly thermally conductive current collector for a secondary battery according to claim 1.

6. The purity of the metal plating layer is 99.8% or more in each case.

2. The highly thermally conductive current collector for a secondary battery according to claim 1.

7. The polymer includes at least one of an insulating polymer material, an insulating polymer composite material, a conductive polymer material, and a conductive polymer composite material, Among them, the insulating polymer material includes at least one of polyamide PA, polyterephthalate, polyimide PI, polyethylene PE, polypropylene PP, polystyrene PPE, polyvinyl chloride PVC, aramid, acrylonitrile-butadiene-styrene copolymer ABS, polybutylene terephthalate PET, polyparaphenylene terephthalamide PPTA, polypropylene PPE, polyoxymethylene POM, epoxy resin, phenolic resin, polytetrafluoroethylene PTEE, polyvinylidene fluoride PVDF, silicone rubber, polycarbonate PC, polyvinyl alcohol PVA, polyethylene glycol PEG, cellulose, starch, protein, derivatives thereof, crosslinked bodies thereof, and copolymers thereof; 2. The highly thermally conductive current collector for a secondary battery according to claim 1.

8. The polymer thin film layer has a thickness ranging from 1 μm to 25 μm, and the metal plating layer has a thickness ranging from 0.5 μm to 1.5 μm.

2. The highly thermally conductive current collector for a secondary battery according to claim 1.

9. A method for producing a highly thermal conductive current collector for a secondary battery according to any one of claims 1 to 8, comprising the steps of: homogeneously mixing the polymer and the silicon carbide particles to form a silicon carbide doped polymeric material; performing a casting operation on the silicon carbide doped polymeric material to form the polymeric thin film layer; and depositing the metal plating layer on each of two opposing surfaces of the polymer thin film layer.

2. A method for producing a highly thermally conductive current collector for a secondary battery, comprising:

10. After casting the silicon carbide-doped polymeric material, a semi-polymeric thin film layer is formed, and the semi-polymeric thin film layer is biaxially stretched and divided to form the polymeric thin film layer. The method for producing a highly thermally conductive current collector for a secondary battery according to claim 9 .